Theory of cortical plasticity - Cooper, Leon N. (World Scientific, 2004)
In Theory of Cortical Plasticity, Nobel Laureate LeonCooper and his collaborators present a systematic development of theBienenstock, Cooper and Munro (BCM) theory of synaptic plasticity, anddiscuss experiments that test both its assumptions and consequences. This insightful book provides an elegant analysis of theoreticalstructure in neuroscience research, and elucidates the role BCM theoryhas played in guiding research leading to our present understanding ofthe mechanisms underlying cortical plasticity.